Membangun Identitas: Kapitan Arab Batavia, 1844-1942 - Ismahan, Ismahan; Humaidi, Humaidi; Abrar (Universitas Hamzanwadi, 2025)
The existence of ethnic Arab descendants in Batavia is an interesting thing to explore, given their status as ethnic migrants, but received a good welcome by the local community. This paper on “Kapitan Arab in Batavia” is a portrait of the social life of ethnic Arab descendants in building and forming a community in Batavia. The study begins in 1844, when Said Na'um was appointed as the first Arab Kapitan, and ends in 1942 with the end of Dutch colonial rule which also formally ended the existence of the Batavian Arab Kapitan. This research is conducted through the historical method, which goes through the stages of topic selection, heuristics, verification, interpretation and historiography.This paper argues that the Arab Kapitan of Batavia had an initial role as a liaison between the policies of the colonial government and the Arab community, as well as seeking progress in the fields of trade and education. However, the hadrami-style stratification pattern in Batavia sometimes triggered conflicts between groups, such as between the Jamiat Kheir and Al Irsyad groups. Among the Arab Kapitans of Batavia, the figure of Kapitan Umar Manggus is important as a community leader who helped drive change. He led the Arab community in the midst of a reform wave that rejected the exclusivity of the sayyids. His background as part of the lower stratification placed him as an agent of change to shape the Batavian Arab community to become more egalitarian. The colonial government's attitude tended to be passive, because not being involved in the vortex of conflict would be more beneficial in maintaining the order.